Students’ Perception and Preference of Problem Based Learning During Introductory Course of a Nepalese Medical School - Ghimire, Satish Raj; Bhandary, Shital (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Problem based learning is considered superior to the conventional didactic teaching for contextual learning, long term retention of knowledge, development of generic skill and attitudes. This study looked in to the students’ perception and preference of problem bases learning in a sixmonth introductory course in the beginning of undergraduate medical school program. Methods: A 20-item questionnaire with four-point rating scale (1-strongly disagree, 2-Disagree, 3-Agree and 4-Strongly agree) was administered to collect first year medical students’ perception on problem based learning during first six month introductory course (June 2010 to November 2010) of first batch of medical students. The questionnaire included 13-items for perception and seven for preferences. It also had an open-ended comment section. Results: Students showed positive reaction problem based learning irrespective of gender or educational background in providing contextual learning and retention of knowledge. Students agreed that it fostered generic skills (communication, group work, critical thinking, reasoning, reflectiveness and self-directed learning). Students wished for more such sessions in more subjects with short content assessment at the end of the sessions. Conclusions: Problem based learning is fun, provides contextual learning and imparts long term retention of knowledge through students’ active participation in a small group. It also promotes generic skills and self-directed life-long learning. Plain Language Summary: The study was conducted to see the effectiveness of problem based learning (PBL) in a six-month long ‘Introductory Course’ of undergraduate medical sciences program. The study found that PBL made topics interesting and created a fun-filled learning environment. It found PBL to be effective in fulfilling learning objectives and making the contents relevant. It also showed PBL to be effective in promoting a set of generic skills and attitudes. Thus, the curricular contents presented in context through PBL can impart meaningful knowledge and a set of generic skills that are important to develop of a habit of self-directed, life-long learning. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13023 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):64-68